Robotic partial nephrectomy for renal tumors larger than 4 cm: a systematic review and meta-analysis. - Liangkuan Bi; Caixia Zhang; Kaiwen Li; Xinxiang Fan; Kewei Xu; Jinli Han; Hai Huang; Hao Liu; Wen Dong; Xiangyun Yang; Jian Huang; Tianxin Lin (PLoS ONE)
Background With the establishment of minimally invasive surgery in society, the robot has been increasingly widely used in the urologic field, including in partial nephrectomy. This study aimed to comprehensively summarize the currently available evidence on the feasibility and safety of robotic partial nephrectomy for renal tumors of >4 cm. Method and findings An electronic database search of PubMed, Scopus, Web of Science, and the Cochrane Library was performed. This systematic review and meta-analysis was based on all relevant studies that assessed robotic partial nephrectomy for renal tumors of >4 cm. Five studies were included. The meta-analysis involved 3 studies from 11 institutions including 154 patients, while the narrative review involved the remaining 2 studies from 5 institutions including 64 patients. In the meta-analysis, the mean ischemic time, operation time, and console time was 28, 319, and 189 minutes, respectively. The estimated blood loss and length of stay was 317 ml and 3.8 days, respectively. The rates of conversion, positive margins, intraoperative complications, postoperative complications, hilar clamping, and collecting system repair were 7.0%, 3.5%, 7.0%, 9.8%, 93.9%, and 47.5%, respectively. The narrative review showed results similar to those of the meta-analysis. Conclusions Robotic partial nephrectomy is feasible and safe for renal tumors of >4 cm with an acceptable warm ischemic time, positive margin rate, conversion rate, complication rate, operation time, estimated blood loss, and length of stay.